Optimizing the number of valid measurements for the attenuation coefficient to assess hepatic steatosis in MAFLD patients: A study of 139 patients who underwent liver biopsy - Li, Xueqi; Huang, Xianjue; Cheng, Guangwen; Liang, Jing; Qiu, Luping; Zhang, Jubo; Yao, Qiyuan; Ding, Hong (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Purpose We investigated the optimal number of valid measurements (VMs) for the attenuation coefficient (AC) to assess liver steatosis using attenuation imaging (ATI) and explored factors that may affect AC measurement in patients with metabolic dysfunction-associated fatty liver disease (MAFLD).Materials and Methods A total of 139 patients with MAFLD who underwent ATI and liver biopsy were enrolled. Hepatic steatosis was graded as S0–3 according to the SAF scoring system. The AC values from 1, 2, 3, 5, and 7 VMs were compared with the degree of liver steatosis. The correlation between AC values from different VMs was analyzed. The diagnostic performance of AC from different VMs at each steatosis grade was compared. The factors related to AC were identified using linear regression analysis.Results The mean AC values from 1, 2, 3, 5, and 7 VMs were not significantly different between grades S0–3 (p=n.s. for all). Bland-Altman analysis showed the mean difference in AC values of 3 VMs and 7 VMs was 0.003 dB/cm/MHz, which was smaller compared with 2 VMs, and close to 5 VMs. The intraclass correlation coefficients of AC were all > 0.90 among different VM groups. AC values from different VMs all significantly predicted steatosis grade ≥S1, ≥S2, and S3 without significant statistical differences (p=n.s. for all). The multivariate analysis showed that the hepatic steatosis grade and triglyceride level were factors independently associated with AC.Conclusion Three valid measurements of AC may be adequate to ensure the accuracy and reproducibility of hepatic steatosis assessment. The degree of liver steatosis and the triglyceride level significantly affected AC values.
Keywords: Metabolic dysfunction-associated fatty liver disease; liver steatosis; attenuation imaging; attenuation coefficient; Metabolic dysfunction-associated steatotic liver disease